2018
DOI: 10.1186/s12891-018-2316-z
|View full text |Cite
|
Sign up to set email alerts
|

What is the association between the presence of comorbidities and the appropriateness of care for low back pain? A population-based medical record review study

Abstract: BackgroundAlthough “non-specific” in 90% of cases, low back pain (LBP) is often treated as an independent entity, even though comorbidities are commonly associated with it. There is evidence that some LBP may be related to chronic conditions or be a symptom of poor health. The purpose of this study was to clarify the extent of comorbidities amongst a cohort of Australian adults with LBP and examine if having concurrent conditions has any association with appropriateness of care for LBP.MethodsA population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 21 publications
(30 reference statements)
1
33
0
Order By: Relevance
“…Finally, there may also be a relationship between chronic disease and chronic pain in athletes. (Ramanathan et al, 2018). However, it is important to note that, due to our cross-sectional design, we cannot establish a cause-effect relationship between chronic disease and GOIs in cyclists.…”
Section: Characteristicsmentioning
confidence: 89%
“…Finally, there may also be a relationship between chronic disease and chronic pain in athletes. (Ramanathan et al, 2018). However, it is important to note that, due to our cross-sectional design, we cannot establish a cause-effect relationship between chronic disease and GOIs in cyclists.…”
Section: Characteristicsmentioning
confidence: 89%
“…Alternatively, patients may adopt a self-perception that LBP is less threatening to one's health or is more self-manageable compared to comorbid health conditions, and are therefore more likely to seek care for the comorbid condition instead (Hurwitz et al, 1999;Idowu et al, 2015). It has also been found that LBP patients with comorbidities are less likely to receive appropriate care for their LBP, compared to LBP patients who do not have comorbidities (Ramanathan et al, 2018). For example, LBP patients with one comorbid condition are less likely to be examined for the presence of red flags (e.g., fractures, cancer, infection), whereas those suffering from three or more comorbidities are at higher risk of being prescribed unnecessary medications and failing to receive appropriate advice for managing their LBP (Ramanathan et al, 2018).…”
Section: Comparison To Literaturementioning
confidence: 99%
“…It has also been found that LBP patients with comorbidities are less likely to receive appropriate care for their LBP, compared to LBP patients who do not have comorbidities (Ramanathan et al, 2018). For example, LBP patients with one comorbid condition are less likely to be examined for the presence of red flags (e.g., fractures, cancer, infection), whereas those suffering from three or more comorbidities are at higher risk of being prescribed unnecessary medications and failing to receive appropriate advice for managing their LBP (Ramanathan et al, 2018). This pattern was mirrored by the significant inverse association we found between a history of diabetes and seeking medical care for LBP, highlighting the complexity of managing LBP in the presence of multimorbidities.…”
Section: Comparison To Literaturementioning
confidence: 99%
“…>65 years old) patients [49], yet this population is commonly excluded from RCTs [6]. Another critical gap in the generalizability of pain RCTs is the recognition that a substantial number of people with chronic pain have multiple pain etiologies and anatomical pain sites, as well as other coexisting multimorbidities [74] that often exclude them from classical RCTs with tight exclusion criteria. These well-recognized problems for RCTsin many areas -reveal a limited understanding of drug-drug, and drug-disease interactions relevant for older, multimorbid populations on multiple medications and require future study.…”
Section: Population-based Research On Chronic Pain Burden and Impact mentioning
confidence: 99%
“…This study found a widespread mismatch between trials and disease burden for musculoskeletal conditions in all income level strata. Furthermore, other differences -with respect to pain prevalence and treatment -in sex/gender [51], race/ethnicity [14;33] and comorbidities [74] suggest other important evidence-burden gaps in real-world pain treatment and research.…”
Section: Population-based Research On Chronic Pain Burden and Impact mentioning
confidence: 99%